Penguasaan Fonologi dalam Pemerolehan Bahasa (Studi Kasus pada Anak Usia 1.5 Tahun): Mastery Of Phonology In Language Acquisition: A Case Study Of Child Aged 1.5 - Wijayanti, Lisma Meilia (Institut Agama Islam Sunan Giri Ponorogo, 2021)
Acquisition of language is a very long process, starting from when the child does not know a language until it is fluent. Mastery of a language by a child begins with acquiring the first language which is often called the mother tongue. Phonological acquisition is a part of language acquisition which is often called language development or growth. This study aims to describe and explain the language acquisition of children aged 1 year and 5 months at the phonological level. This study used a descriptive research design combined with a case study approach. The main data source was the research subject (Rhanidya, 1.5 years old), while the additional data source was Mrs. Rhanidya. The data in this study are utterances that come out of Rhanidya's sense of utterance. While the data collection techniques used by researchers are interview, observation, peer and note-taking techniques. From the results of the analysis of phonological acquisition, it was found that 34 words had been mastered by the research subjects. The 34 words are divided into vowels and consonants and vowel phonemes and consonants from Indonesian and Javanese. The results also show that the acquisition of language in children in the phonological aspect is influenced by environmental factors, especially family, this is indicated by the large number of vocabulary they get in the family environment and around them. Children are also able to pronounce some nouns, verbs, and adjectives.